Neurologic and neuroimaging findings in patients with COVID-19: A retrospective multicenter study. (29th September 2020) - Kremer, Stéphane; Lersy, François; Anheim, Mathieu; Merdji, Hamid; Schenck, Maleka; Oesterlé, Hélène; Bolognini, Federico; Messie, Julien; Khalil, Antoine; Gaudemer, Augustin; Carré, Sophie; Alleg, Manel; et al.
Abstract : Objective: To describe neuroimaging findings and to report the epidemiologic and clinical characteristics of patients with coronavirus disease 2019 (COVID-19) with neurologic manifestations. Methods: In this retrospective multicenter study (11 hospitals), we included 64 patients with confirmed COVID-19 with neurologic manifestations who underwent a brain MRI. Results: The cohort included 43 men (67%) and 21 women (33%); their median age was 66 (range 20–92) years. Thirty-six (56%) brain MRIs were considered abnormal, possibly related to severe acute respiratory syndrome coronavirus. Ischemic strokes (27%), leptomeningeal enhancement (17%), and encephalitis (13%) were the most frequent neuroimaging findings. Confusion (53%) was the most common neurologic manifestation, followed by impaired consciousness (39%), presence of clinical signs of corticospinal tract involvement (31%), agitation (31%), and headache (16%). The profile of patients experiencing ischemic stroke was different from that of other patients with abnormal brain imaging: the former less frequently had acute respiratory distress syndrome ( p = 0.006) and more frequently had corticospinal tract signs ( p = 0.02). Patients with encephalitis were younger ( p = 0.007), whereas agitation was more frequent for patients with leptomeningeal enhancement ( p = 0.009). Conclusions: Patients with COVID-19 may develop a wide range of neurologic symptoms, which can be associated with severe and fatal complications such as ischemic stroke or encephalitis. In terms of meningoencephalitis involvement, even if a direct effect of the virus cannot be excluded, the pathophysiology seems to involve an immune or inflammatory process given the presence of signs of inflammation in both CSF and neuroimaging but the lack of virus in CSF. ClinicalTrials.gov identifier: NCT04368390.